Remaja Sehat dari Desa: Edukasi Gizi dan Pencegahan Anemia melalui Video Animasi di Festival Karya Anak Desa Harjomulyo - Septiani, Baiq Dewi Sukma; Indraswari, Sonya Hayu; Safitri, Erwina; Fitriyah, Holif; Ervyanna, Ellanda Rima (Yayasan Inspirasi El Burhani, 2025)
Introduction: Anemia remains a significant health problem in Indonesia, particularly among adolescents. Based on the 2023 Indonesian Health Survey (SKI), the prevalence of anemia among adolescents aged 15-24 years reached 15.5%, with slightly higher rates for females at 18% and 14.4% for males. Objective: To increase public awareness, understanding, and positive behavioral changes regarding the importance of nutrition in early anemia prevention. Objective: To increase public awareness, understanding, and positive behavioral changes regarding the importance of nutrition in early anemia prevention. Method: The Community Service activity, part of the Village Children's Work Festival, was attended by 30 adolescents aged 12-18 years. Educational materials focused on the importance of nutrient consumption to prevent anemia, with an emphasis on iron and vitamin C intake, as well as foods that inhibit or support iron absorption. A 7-minute animated educational video on nutrition to prevent anemia was projected using a projector and delivered with simple, engaging narration tailored to the characteristics of adolescents. Following the video, an interactive question-and-answer session and group discussion were held to strengthen participants' understanding. Result: Based on the results of measuring adolescents' understanding before and after being given nutrition education through animated video media, data obtained showed that the average pre-test score for understanding anemia prevention was 52.83 with a standard deviation of 8.57. After the intervention in the form of showing educational animated videos and discussion sessions, the average post-test score increased to 74.17 with a standard deviation of 6.95. Statistical analysis using paired sample t-test showed a p-value = 0.000, which means there was a statistically significant difference between the pre-test and post-test scores (p < 0.05). These results indicate that animated video-based nutrition education effectively increased participants' understanding of anemia prevention efforts. Conclusion: Animated video media is an effective educational method and can be used as a nutritional health promotion strategy among adolescents, especially in anemia prevention efforts.